2008
DOI: 10.4161/cib.1.2.7146
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the host cytoskeleton by the intracellular pathogenChlamydia trachomatis

Abstract: Chlamydiae are obligate intracellular pathogens that cause a wide range of human diseases. Chlamydia resides in a membrane bound vacuole ("inclusion") that expands to accommodate replicating bacteria. We recently reported that Chlamydia remodels and recruit two major cytoskeletal components of the host cell-F-actin and Intermediate filaments-to form a dynamic scaffold that provides structural stability to the inclusion. As the inclusion expands, a secreted chlamydial protease progressively modifies the interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…As further evidence of the isolation of distinct populations of chlamydial forms, we compared the ability of isolated persistent forms vs. EBs to generate a normal infection in a suspension culture as indicated by the ability of L929 cells to adhere to cover slips. Cell adherence is a good indicator of infection as infectious EBs of C. trachomatis genital strains can release cytotoxic and host modulatory factors that disrupt the cytoskeleton of host cells, thus preventing host cell attachment to coverslips post-infection (Moulder et al, 1976; Belland et al, 2001; Carabeo et al, 2002; Clifton et al, 2004; Kumar and Valdivia, 2008). As demonstrated by Figure 3e, only those cells incubated with the non-infectious persistent form were able to adhere to coverslips.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…As further evidence of the isolation of distinct populations of chlamydial forms, we compared the ability of isolated persistent forms vs. EBs to generate a normal infection in a suspension culture as indicated by the ability of L929 cells to adhere to cover slips. Cell adherence is a good indicator of infection as infectious EBs of C. trachomatis genital strains can release cytotoxic and host modulatory factors that disrupt the cytoskeleton of host cells, thus preventing host cell attachment to coverslips post-infection (Moulder et al, 1976; Belland et al, 2001; Carabeo et al, 2002; Clifton et al, 2004; Kumar and Valdivia, 2008). As demonstrated by Figure 3e, only those cells incubated with the non-infectious persistent form were able to adhere to coverslips.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…The inclusion expansion has been suggested to be dependent on host cell lipid metabolism (Derre et al, 2011;Robertson et al, 2009), host cell cytoskeletal proteins, vimentin and actin (Kumar and Valdivia, 2008a), and secreted bacterial effector proteins (Jorgensen and Valdivia, 2008;Mital et al, 2013), which may manipulate processes in the host cytoplasm that are required for optimal inclusion expansion. It is possible that expansion of the chlamydial inclusion is linked to bacterial replication (Fields and Hackstadt, 2002;Kumar and Valdivia, 2008b), and in fact, inclusion area has been used to indirectly measure chlamydial replication and growth (Engström et al, 2013;Nguyen et al, 2011;Tietzel et al, 2009;Volceanov et al, 2014). However, a potential link between inclusion expansion and bacterial replication has not been proven experimentally or characterized under different growth conditions.…”
Section: Introductionmentioning
confidence: 97%
“…In this work, we confirmed and further characterized that infection blocks cell migration (Kumar and Valdivia, ). Live cell microscopy of infected and control cells revealed that the velocity of motile epithelial cells is reduced upon C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 97%
“…). It has been shown previously that Chlamydia infection can block cell migration in an in vitro wound healing assay (Kumar and Valdivia, ). However, the functional consequences of Chlamydia ‐induced remodelling of the GA remain elusive.…”
Section: Introductionmentioning
confidence: 99%